Encephalotrigeminal angiomatosis: an atypical presentation of a rare disease - Ananya T., Sai Lakshmi; Kumar, Radha (International Journal of Contemporary Pediatrics, 2017)
Encephalotrigeminal angiomatosis also called as Sturge Weber Syndrome (SWS) is a sporadically occurring rare congenital neuro cutaneous disorder. Unilateral facial portwine stain along with contralateral focal seizures and ipsilateral leptomeningeal angiomatosis is considered as diagnostic of Sturge Weber Syndrome. Capillary malformation along the ophthalmic and maxillary divisions of the trigeminal nerve is common in this condition. MRI with contrast is the imaging modality of choice for the diagnosis. The current report describes a case of a 9-month-old infant with atypical presentation of Type 1 Encephalo-trigeminal angiomatosis with complications. The clinicopathological and radiographic features and differential diagnosis are discussed.